Role of Radial Endoscopic-ultrasound (EUS) to Establish Diagnosis of Undetermined Causes of Obstructive Jaundice: A Case Series - Eka Surya Nugraha; Dolvy Girawan; Nenny Agustanti; Yudi Wahyudi; Muhammad Begawan Bestari (The Indonesian Society for Digestive Endoscopy, 2019)
Identification the causes of obstructive jaundice are challenging. Recent radiologic imaging techniques improve diagnostic yield to determine jaundice causes. However, small lesions particularly in pancreas or periampullary area that lead to jaundice, often unrecognize with conventional radiologic imaging. Radial endoscopic-ultrasound (EUS) is the most sensitive modality to identify the lesions-related obstructive jaundice, remarkably in the lack of high-resolution radiologic facilities. We presented four cases of obstructive jaundice, without obvious obstruction causes from conventional radiologic imaging or abdominal ultrasound. All patients underwent radial EUS, pancreatic head mass revealed in 2 patients, and distal stenosis of the common bile duct without evidence of mass was found in 2 other patients. The masses size were 16 mm and 39 mm in diameter. Due to linear EUS and EUS guided fine needle were unavailable in our center, confirmation biopsy was undone. Three patients were performed endoscopic retrograde cholangiopancreatography (ERCP) for dilatation and inserting stents, and one patient referred to the surgeon. In conclusion, radial EUS aided to diagnose the definite causes of jaundice despite in the less-equipped of high-resolution radiologic imaging.